Effect of carboxymethyl konjac glucomannan coating on curcumin-loaded multilayered emulsion: stability evaluation - Luhui Wang; Xinru Zhang; Junxia Xiao; Jiayi Shi (Food Science and Human Wellness)
The stability against various environmental stresses of the curcumin-loaded secondary and tertiary emulsions that was emulsified by whey protein isolate (WPI) and coated by chitosan (CHI), carboxymethyl konjac glucomannan (CMKGM), or their combination through layer-by-layer assembly was investigated. Generally, the multilayered emulsions were destabilized in high NaCl concentrations or medium pH that could interrupt the electrostatic interaction between the three polyelectrolytes or deprotonate CHI, indicating that electrostatic interaction played an important role in the stability of emulsions. Compared with the primary emulsion that was solely stabilized by WPI, extra coating with CHI and CMKGM generally increased the stability of the emulsion against repeated freezing-thawing, improved the retention of curcumin against heating, UV irradiation, and long-term storage, and the effects were more remarkable in the tertiary emulsion with CMKGM locating in the outmost layer. Since CMKGM has shown the colon-targeted delivery potency, the multilayered emulsions assembled by layer-by-layer deposition, especially the tertiary emulsion, could be used as an effective carrier for the targeted delivery of curcumin.